2022
DOI: 10.1128/jvi.01360-22
|View full text |Cite
|
Sign up to set email alerts
|

Expression Ratios of the Antiapoptotic BCL2 Family Members Dictate the Selective Addiction of Kaposi’s Sarcoma-Associated Herpesvirus-Transformed Primary Effusion Lymphoma Cell Lines to MCL1

Abstract: Primary effusion lymphoma (PEL) is caused by Kaposi’s sarcoma-associated herpesvirus. We showed previously that PEL cell lines require the antiapoptotic protein MCL1 for survival but not the other BCL2 family proteins.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…S63845 was also tested against KHSV [182]. As previously mentioned, this virus is associated with PEL, an aggressive B-cell cancer.…”
Section: Agent(s)mentioning
confidence: 99%
See 3 more Smart Citations
“…S63845 was also tested against KHSV [182]. As previously mentioned, this virus is associated with PEL, an aggressive B-cell cancer.…”
Section: Agent(s)mentioning
confidence: 99%
“…As previously mentioned, this virus is associated with PEL, an aggressive B-cell cancer. This disease is characterized by very poor survival accompanying the high resistance to conventional chemotherapeutic treatments [120], which has motivated scientists to search for more effective antioncogenic agents [182]. Dunham et al [182] revealed that S63845 induced apoptosis in KHSV-positive as well as KHSV-and EBV-positive cells, BC3 and BC1, respectively.…”
Section: Agent(s)mentioning
confidence: 99%
See 2 more Smart Citations